2021
DOI: 10.1093/pch/pxab080
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of rounds on a general paediatric ward: Implementation of a checklist to improve efficiency, quality of rounds, and family satisfaction

Abstract: Objective The purpose of this study was to develop a standardized rounding tool for use on the general paediatric ward and to determine if its use can improve quality of rounds as well as patient and parent satisfaction. Methodology The study used a pre- and post-intervention prospective observational methodology. The intervention consisted of the implementation of a Checklist Rounding Tool (CRT) entitled the ‘Paediatric Inpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Subjective improvements in staff and patient communication were demonstrated with the use of checklists or proformas during the surgical ward round [ 13 , 27 , 29 , 32 , 34 ]. Documentation during the ward round is an important means of communication between clinical teams, with improvements in communication shown to mitigate medical errors and improve patient safety and outcomes [ 2 , 9 , 38 , 48 , 49 ]. Future studies should aim to develop more objective measures of staff and patient communication to improve assessment of different perioperative quality improvement strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective improvements in staff and patient communication were demonstrated with the use of checklists or proformas during the surgical ward round [ 13 , 27 , 29 , 32 , 34 ]. Documentation during the ward round is an important means of communication between clinical teams, with improvements in communication shown to mitigate medical errors and improve patient safety and outcomes [ 2 , 9 , 38 , 48 , 49 ]. Future studies should aim to develop more objective measures of staff and patient communication to improve assessment of different perioperative quality improvement strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Checklists serve as a platform to empower junior doctors to ask important questions regarding patient care in an otherwise intimidating environment [27]. The overall perception of ward round checklists (from this systematic review and previous studies) is positive [30, 49–53]. However, some clinical staff are hesitant incorporate checklists into the ward round as they feel it will increase time spent on the ward round [54].…”
Section: Discussionmentioning
confidence: 99%
“…However, two out of three studies reporting on time taken during ward rounds demonstrated a reduction in time taken when checklist was used [7, 28]. Other studies that have implemented checklists during ward rounds have shown that there was either no difference or less time spent on ward rounds [5, 53, 57, 58]. Time limitations should not be an issue when checklists are designed well.…”
Section: Discussionmentioning
confidence: 99%